Differential sensitivity of offspring from four species of goodeine freshwater fish to acute exposure to nitrates - Villa-Villaseñor, Ivette Marai; Yáñez-Rivera, Beatriz; Rueda-Jasso, Rebeca Aneli; Herrera-Vargas, Ma. Antonia; Hernández-Morales, Rubén; Meléndez-Herrera, Esperanza; Domínguez-Domínguez, Omar (Frontiers in Ecology and Evolution, 2022)
Nitrate-nitrogen (NO3-N) pollution related to anthropogenic activities is increasing in freshwater ecosystems. Knowledge about NO3-N sensitivity in freshwater wild fish is needed to understand the differential tolerance between species. Goodeinae is a subfamily of 41 endemic fishes that inhabit central Mexico, with 33 species in the IUCN red list and three extinct. Distributional patterns suggest tolerant and sensitive goodeines related to the conservation gradient of freshwater ecosystems. Four species with a differential distribution and tolerance were selected to evaluate their physiological responses to NO3-N. Fish were exposed to different NO3-N concentrations for 96 h and the median lethal concentration (LC50) was determined. Swimming disorders plus gill and liver histopathological indexes were estimated and incorporated into an Integrated Biomarker Response for each species. Skiffia lermae (LC50= 474.332 mg/L) and Xenotoca variata (LC50= 520.273 mg/L) were more sensitive than Goodea atripinnis (LC50= 953.049 mg/L) and Alloophorus robustus (LC50= 1537.13 mg/L). The typical histological damage produced by NaNO3-N exposure was fusion of secondary lamellae in gills. This was present in all species and cellular degeneration was observed at the highest concentrations. Secondary lamellae aneurysms were only observed in G. atripinnis. Liver alterations included vascular dilation in hepatic sinusoids, hyperemia and nuclear hypertrophy; higher concentrations produced hepatocyte cytoplasmic vacuolation and reduced frequency of cell nuclei. Behavioral and histopathological alterations could explain the differential species sensitivity. The results suggest that species which preserve gill function and transfer the task of detoxification to the liver might have the best chance of surviving in polluted environments. Moreover, species previously considered as tolerant may be highly susceptible to NaNO3-N exposure. Therefore, it is necessary to closely monitor NaNO3-N concentrations in freshwater ecosystems and, if possible, reduce their levels to avoid the loss of wild populations.